Effect of Oxygen Pressure on Transport Propeties of Al-doped ZnO Films Grown by PED - Sang, Ngo Dinh; Quang, Pham Hong; Ngoc, Do Quang (Communications in Physics, 2012)
Al-doped ZnO films were grown by pulsed electron deposition (PED) at room temperature and 400 oC and at the oxygen pressure ranged from 3 mTorr to 20 mTorr. Transport properties were measured by van der Pauw technique. Crystallinity of the films was characterized by X-ray diffraction. It was found that the films grown at room temperature have a very high resistivity due to poor crystallinity. For the films grown at 400 o C, the obtained results indicate that the film grown at a lower pressure has a higher carrier mobility as well as a higher carrier concentration, resulting in a lower resistivity. This phenomenon has been discussed in term of the concentration of oxygen vacancies and the number of traps for carriers.